P079: Clinical handover from emergency medical services to the trauma team: A gap analysis. (May 2020) - Javidan, A.; Nathens, A.; Tien, H.; da Luz, L.
Abstract : Background: Clinical handover between emergency medical services (EMS) and the hospital trauma team can be subject to errors that may negatively affect patient care. Thus far, there has been limited evaluation of the quality of EMS handover. As such, we sought to characterize handover practices from EMS to the trauma team, identify areas for improvement, and determine if there is a need for standardization of current handover practices. Aim Statement: Identify areas for improvement in handover from EMS to the trauma team, specifically examining handover content, structure, and discordances between different team members regarding handover expectations. Measures & Design: Data were prospectively collected over a nine week period by a trained observer at Canada's largest level one trauma centre. A randomized scheduled was used to capture a representative breadth of handovers. Data collected included outcome measures such as duration of handover, structure of the handover, and information shared, process measures such as questions and interruptions from the trauma team, and perceptions of the handover from nurses, trauma team leaders (TTLs) and EMS according to a bidirectional Likert scale. Evaluation/Results: Of 410 trauma team activations, 79 verbal handovers were observed. Information was often missing regarding airway (present 22%), breathing (54%), medications (59%), and allergies (54%). Handover structure lacked consistency beyond the order of identification and mechanism of injury. Only 28% of handovers had a dedicated question and answer period. Of all questions asked, 35% were questioning previously given information. EMS returned to categories of information unprompted in 84% of handovers. The majority of handovers (61%) involved parallel conversations between team members while EMS was speaking, which was associated with a greater number of interrupting questions from the trauma team (3.15 vs. 1.82, p =.001). There was a statistically significant disparity between the self-evaluation of EMS handovers and the perceived quality determined by nurses and trauma team leaders. Discussion/Impact: At our trauma centre, we have identified the need for handover standardization due to poor information content, a lack of structure and active listening, significant information repetition, and discordant expectations between EMS, nurses, and TTLs. We intend to use our results to guide the development of a co-constructed framework integrating the perspectives of all team members on the trauma team.